Optimizing Cooling Tower Length Fan Blade Standardization in Biodiesel Plants: Approach to Cost Savings and Efficiency Improvement - MOHAMAD ZAMRI, MUHAMMAD HAZMIE; Mohd Faizal Esa (Research Progress in Mechanical and Manufacturing Engineering, 2026)
Cooling towers play a crucial role in dissipating heat from industrial processes, especially in biodiesel plants where thermal management is essential. However, the diversity of fan blade lengths currently in use results in increased maintenance complexity, higher inventory costs for spare parts, and inconsistent energy performance. This study addresses the challenge of optimizing cooling tower fan blade design by proposing a standardized blade length that can deliver a balance between operational efficiency and cost-effectiveness across biodiesel facilities. The main objectives of this research are to investigate the performance of standard cooling tower designs, to develop a new blade length configuration, and to evaluate its efficiency compared to existing setups. To achieve these goals, three different blade lengths 0.7 m, 1.0 m, and 1.5 m were analyzed using Computational Fluid Dynamics (CFD) simulations conducted in ANSYS Fluent. The simulations measured critical parameters such as generated torque, airflow velocity, and energy consumption under constant rotational speed (500 RPM). A systematic comparison was made to determine the best-performing design in terms of both energy output and cost savings. Results indicated that the 1.5 m blade length demonstrated the highest efficiency with the lowest cost per unit airflow, generating a torque of 8107.30 Nm and a power consumption of 424.42 kW. Conversely, the 0.7 m and 1.0 m blades offered reduced torque and airflow, but showed potential for further optimization through aerodynamic enhancements. Despite its superior performance, the longer blade increases operational and material costs, which must be weighed against energy benefits. In conclusion, while standardizing to a 1.5 m blade offers the best performance, the study highlights the importance of balancing energy efficiency with maintenance simplicity and cost. The findings provide strategic insights for biodiesel plants seeking to streamline operations and enhance system sustainability. This research also lays the foundation for broader standardization efforts in industrial mechanical systems.